Comprehensive investigation of an Arctic rain on snow event: impacts on the chemical and physical properties of the seasonal snowpack in Svalbard - Monzali, Matteo (Alma Mater Studiorum - Università di Bologna, 2023)
The cryosphere is a vital component of the Earth system. It comprehends all the frozen water bodies on our planet, and results crucial when talking about climate and climate change. Polar regions are essential since the phenomenon of polar amplification makes them very sensitive to small changes in global mean air temperature. One of the most studied polar areas is the Svalbard archipelago, located at around 81 °N. There, the town of Ny-Ålesund hosts many polar research groups, so that many data are available for that specific area. Rain On Snow (ROS) events are a particular kind of weather event with rain falling over the snowpack during winter months. Their frequency is expected to increase with climate change, but due to their past uncommonness, they are still not well studied. The effects of these events are various as they influence different components of the cryosphere, from the snowpack to the sea ice, but many are still not known or well characterized. The aim of this work is to collect data from many different sources, to carry out a comprehensive analysis of a ROS event that happened in Ny-Ålesund during March 2022, including its genesis and its consequences. The different sources include data from automatic weather stations, two reanalyses, satellite, and manual samples of the snowpack, so that many aspects of the cryosphere are considered. The results showed that the air mass originated from the Gulf of Mexico and was transported to Svalbard by a particular geopotential configuration. No significant amount of anthropogenic compounds has been found from the chemical analyses, while remarkable effects both on the snow and sea surface temperature have been noted, as well as an important decrease in the sea ice. Thanks to these results, aimed research could be undertaken to study specific effects, so that the consequences of ROS events can be well characterized, in the perspective of their increasing frequency in the future.